Evaluation of Online Measuring Gear Tooth Profile Error based on Gear Grinding Machine - Wang Zhonghou; Ma Yahe; Liu Xinrong; Cao Huan (Jixie chuandong)
There is a big space to improve measurement accuracy. Based on the oriented form grinding involute gear online measurement problem,combining with the characteristics of tooth profile measurement,the tooth profile measuring method and the model of error calculation are introduced. The improved least squares residuals of time series analysis method is selected to evaluate the measurement error. The experimental result shows that the residuals of time series analysis method is lower,the fitting curve is closer to the actual value and the method has higher precision of evaluation.